The Variation of Gravity within Countries (or 15 Reasons Why Gravity Should Be Estimated with Domestic Trade Flows) - Yoto V. Yotov (Center for Economic Studies and Ifo Institute (CESifo), 2021)
The gravity equation is the workhorse model for analysis of bilateral trade flows. Despite solid theoretical foundations and clear gains from theory-consistent policy analysis, there are still gaps between gravity theory and empirics. This paper focuses on domestic trade flows, and I argue that there are significant benefits from adhering to theory by estimating gravity equations with domestic (in addition to international) trade flows. To this end, I review the contributions from the related literature and I synthesize them into fifteen arguments for using domestic trade flows in gravity estimations. The survey of the literature reveals the need for further theory contributions and new data developments, and points to opportunities for more empirical analysis and policy applications.
Keywords: F13; F14; F16; 330; domestic trade flows; structural gravity; trade policy; estimation